Assessment of the Robustness of a Color Monitoring Chart Calibration Method for Crowdsourcing-Based Preventive Conservation - Miguel Antonio Barbero-Álvarez; José Manuel Menéndez; Juan Antonio Rodrigo; Blanca Ramírez-Barat; Emilio Cano (Applied Sciences, 2021)
Monitoring environmental factors such as pollutants, relative humidity, light, etc. is needed to ensure a proper preventive conservation of cultural heritage. Since existing systems are expensive and difficult to maintain, we propose as a sustainable alternative the use crowdsourced photographs taken by visitors using their cell phones. These images of a tailor made panel, including sensitive materials and a calibration color chart, are calibrated and colorimetric information extracted from them. The aim of this paper is assessing the robustness of the color chart and the calibration method used, and evaluating how the ageing of the materials of the chart can affect the accuracy of the calibration process. A choice is made between four candidate materials and a set of industrial inks. Several tests have been performed and mathematical metrics extracted, so the most suitable material is adequately selected. It has been checked how the image calibration process, employed for homogenizing information from the crowdsourced pictures, performs with real-life materials and colors to assess the possible degradation that may happen. This work is a part of a bigger project with the aim of building a crowdsourcing-based monitoring system for preventive conservation of cultural heritage.